SMEs and Certified Management Standards: The Effect of Motives and Timing on Implementation and Commitment. Issue 1 (12th February 2016) - Iatridis, Konstantinos; Kuznetsov, Andrei; Whyman, Philip B.
ABSTRACT: Existing research on certifiable management standards (CMS) and corporate social responsibility (CSR) tends to focus on large companies and is characterised by disagreement about the role of these standards as drivers of CSR. We contribute to the literature by shifting the analytical focus to the behaviour of small and medium-sized enterprises (SMEs) that subscribe to multiple CSR related standards. We argue that, in respect of motive and commitment, SMEs are not as different from large companies as the literature suggests, as they are guided by similar institutional and economic motives. Results, based on ISO 9001, ISO 14001 and OHSAS 18001 certified SMEs in Greece, demonstrate that later adopters are more susceptible to coercive and mimetic motives and are less likely to commit fully to the CMS requirements, while earlier adopters react to normative motives and considerations of internal efficiency gains and tend to carry out CMS requirements with greater diligence.